A4_3 Habitable Dyson Sphere - Shaw, Elliott; Tudor, Vlad; Winkworth, David (Physics Special Topics, 2012)
Dyson Freeman described the concept of the Dyson Sphere in the paper "Search for Artificial Stellar Sources of Infra-Red Radiation" [1]. This is a spherical structure built around a star by a technologically advanced civilization, designed to collect the energy output of its host star. This report explores the possibility of creating artificial gravity via rotation on a Dyson Sphere made of multi-layer graphene. By knowing the ultimate tensile strength of graphene, a maximum equatorial velocity can be calculated, and used to create artificial gravity. The maximum achievable acceleration is found to be ~0.01% of the gravity on Earth, which is barely noticeable.